On the Allocation of Resources in Developing East Asia and Pacific - De Nicola, Francesca; Kehayova, Vera; Nguyen, Ha (World Bank, Washington, DC, 2018)
Over the past decades, East Asia and Pacific's productivity has been gradually catching up with the frontier (the United States), with China leading the pack. Productivity growth has been driven by sustained within-sector productivity growth. Reallocation of labor to sectors with higher productivity, such as industry and services, also contributed to productivity improvements. Nevertheless, resource misallocation remains. Firm-level evidence from four East Asia and Pacific countries (Indonesia, Malaysia, the Philippines, and Vietnam) suggests that resource misallocation across firms within a sector is large, albeit declining over time. Private domestic firms and firms with higher productivity face larger distortions.